Analysis of The Influence of Service Quality, Product features, and Promotion on Customer Satisfaction - Siregar, Ummi Kalsum; Zebua*, Yuniman; Elvi Rambe, Bhakti (Universitas Syiah Kuala, 2024)
The development of an online business is getting faster, making the Shopee Marketplace the most in visitor sales centers in August 2022 according to Similarweb. Consumer Satisfaction on the Shopee marketplace can be affected by the Service Quality, Product Features, and good Promotion. The purpose of this study is to determine the Service Influence Analysis, Product Features, and Promotional against Consumer Satisfaction on the Shopee Marketplace. The population in this study were all users of the Shopee marketplace, as well as Sample in this study were 100 respondents. The techniques used in sampling are total sampling technique. Data collection uses instruments that form a questionnaire through google form to get results from the research variable. In this study, the data analysis technique used by using SmartPLS software (Least Square partial) which is an analysis of the structural equation which is based on variant can simultaneously test the structural model. The test results in this research hypothesis prove that the Quality Service Variables, Product Features, and Promotion has a significant effect on Consumer Satisfaction.